2017
DOI: 10.1590/1807-2577.10417
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of the effects of corticotomy on induced orthodontic movement in rats

Abstract: ResumoIntrodução: A corticotomia alveolar é um procedimento cirúrgico utilizado para aumentar a velocidade do movimento dentário. Objetivo: Identificar evidências histológicas do efeito da corticotomia no movimento ortodôntico no rato. Material e método: Quarenta e cinco ratos Wistar (Rattusnorvegicus Albinus) foram igualmente divididos em três grupos: Grupo de Controle (GC) -sem movimento dentário ou corticotomia; Grupo de movimento (GM) -apenas movimento ortodôntico do dente; e Corticotomia e Movimento Grupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The findings of this study supported earlier research by showing the highest increase in the number of osteoclasts was during the early stages of tooth movement and gradually decreased in the second and third weeks. The highest increase during the first week after orthodontic tooth movement combined with corticotomy was related to the maximum catabolic activity [ 21 , 22 ]. However, some previous research demonstrated that corticotomy and orthodontic tooth movement raised the number of osteoclast cells to their maximal level in the second week before declining [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study supported earlier research by showing the highest increase in the number of osteoclasts was during the early stages of tooth movement and gradually decreased in the second and third weeks. The highest increase during the first week after orthodontic tooth movement combined with corticotomy was related to the maximum catabolic activity [ 21 , 22 ]. However, some previous research demonstrated that corticotomy and orthodontic tooth movement raised the number of osteoclast cells to their maximal level in the second week before declining [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%